Android-Based Drug Information Application Using Augmented Reality Technology - Muhammad Khalis; Dahlan Abdullah; Zalfie Ardian; Muhammad Abi Berkah Nadi; Meutia Nadia Karunia; Abdurrozzaq Hasibuan (International Journal of Engineering, Science and Information Technology, 2024)
The use of Augmented Reality technology in the pharmaceutical sector, particularly in pharmacies, has introduced significant innovations in providing drug information to consumers. AR applications can help healthcare workers and patients better understand drug use through three-dimensional visualization superimposed on the real environment. Observations at Sultan Abdul Aziz Syah Peureulak Hospital indicate that 70% of patients still experience confusion regarding the drug information provided by pharmacy staff. This difficulty is caused by the complexity of the information, lack of personal interaction, or low health literacy. To address this problem, the Android-based Mediscan application was developed using AR technology. This application utilizes Unity and Vuforia Engine software to present drug information visually in card form via the smart device screen. Users can point the camera at a particular drug and receive complete information regarding general indications, dosage, drug class, contraindications, and side effects. This research aims to develop the Mediscan application, calculate the level of patient understanding, measure consumer satisfaction, and evaluate the impact of using AR in presenting drug information. The System Development Life Cycle methodology with the Waterfall model was used in this research. The results show that AR technology can be implemented in Android-based applications to present drug information visually and interactively. The majority of patients feel more informed and gain a better understanding of the medication they are taking. AR technology in the Mediscan application improves user experience, supports the education and training of medical personnel and patients, and enhances the quality of healthcare services in hospitals. This application also makes it easier for medical personnel and pharmacists to convey drug information more effectively and efficiently.